Off and Online Journalism and Corruption International Comparative Analysis - Ibrahim Hamada, Basyouni; Wok, Saodah (IntechOpen, 2020)
This book provides a new theoretical framework of determinants that interact together in five hierarchical levels to restrain or produce corruption. The theory suggests a multilevel analysis that tests hypotheses regarding the relations of journalism and corruption within each level and across levels in international comparative research designs. Corruption as the abuse of power for private gain is built into the journalistic, economic, political, and cultural structures of any society and is affected by its interaction within the international system. The important questions of how differences in corruption across countries can be explained or what makes it more or less in a particular society and how press freedom and social media contribute to the fight against corruption are still unanswered. This book represents a significant contribution on the way to answer these critical questions. It discusses a variety of journalism-corruption experiences that provide a wealth of results and analyses. The cases it examines extend from Cuba to Algeria, India, Saudi Arabia, Sub-Saharan African, Gulf Cooperation Countries, Arab World, and Japan. The primary contribution of this book is both theoretical and empirical. Its details as well as the general theoretical frameworks make it a useful book for scholars, academics, undergraduate and graduate students, journalists, and policy makers.